Economical Electricity Home System using Solar - Azahar, Aisha AJeerah; Mohd Jamail, Nor Akmal; Mat Isa, Amal Hayati; Md Sani, Fatin Nazirah; Mohd Razali, Danial Hakim; Busu, Muhammad Badrul Munir; Kamarudin, Qamarul Ezani (Journal of Electronic Voltage and Application, 2021)
Economical home system can be defined as one realization of home that have a cost-effective ideal by using specific set of technologies combined with the renewable energy as a power supply. This system has a highly advance for lighting, temperature control, socket and own power supply by using solar panel. This system is developed in this project and focused on B40 community that represents the bottom 40% of income earners and also this project becomes suitable for this community for getting an energy efficiency system. Due to the COVID-19, B40 households were reported to have lost their jobs causing financial hardship and had to face the issue of high electricity bills which are very burdensome for them at all in order to pay the cost electricity for monthly. The aim of the article is to design and simulate the solar power system including battery storage in suitable software for a residential house especially in B40 community home and also to analyze the potential of battery storage in order to store the energy from solar panel. Therefore, the economical electricity home system using solar energy for B40 community is proposed in this project for producing an energy efficient system at home. In addition, an electrical floor plan and floor plan of B40 community home is designed in the SketchUp software that using basic electrical equipment such as lighting, ceiling fan and socket. The system is developed by using the MATLAB software in order to produce the result of energy efficiency by using the renewable energy which is solar system and also battery storage. According to the data produced from the calculation of old bills and new bills, the energy consumptions are calculated and also be compared before and after using the renewable energy which is using solar system. The data obtained through calculation of maximum demand in new bill is used in the simulation of solar system in MATLAB software. The results obtained show that after using an energy-efficient load, the monthly new bill is around RM 27.79 which is around RM 10.75 less than the monthly old bill before using an energy-efficient load. It can be concluded that the use of renewable energy in B40 community home can save the energy and also money.